Kinerja Modsecurity Technical Report (Studi Kasus: Pencegahan terhadap Serangan SQL Injection) - Farid Ridho (Jurnal Aplikasi Statistika & Komputasi Statistik, 2015)
Several Measures are impelemented in web application security lifecycle such as Secure Development, Secure Deployment and Secure Operation. In secure operation section, a web application that has been through the stages of development and testing will soon enter production phase. At this stage it will be applied to Web Application Firewall (WAF) that meant to protect application from a malicious request.The purpose of this research is to explore ModSecurity WAF implementation. WAF ModSecurity is a free, open source application that can be used to make the filter to requests which occur on a web application including a request containing SQL Injection commands. Another aim is to see whether the ModSecurity installation on a web server affect the performance of the web server.From the test results concluded that ModSecurity can filter SQL injection and installation of ModSecurity does not significantly affect the performance of the web server.